A docência do século XXI: formando competências para o uso das TIC s na UFPB. - Bezerra, Lebiam Tamar Silva (2006)
This research is an interpretative analysis that studies a case and it was developed from a qualitative approach of the problem of teacher s formation, with the objective of making an analysis of the professional competence construction for the use of technologies of information and communication during the process of formation of the pedagogue. The research presents an historical review of the appearing of the technologies of information and communication (TIC s), of the society of information and knowledge and of the Brazilian s politics about Information in education; it discusses the reconstruction of the professional teacher based on the approach of competences and on the changes of the scientific thinking; it analyses the concepts and usage of the TIC s from talks with managers, teachers and students from the course of Pedagogy of Paraíba Federal University. It was taken into account that the continuous formation or that in service face bigger spacial and temporal challenges of form and contents that aren t favorable to the development of the teacher s competences for the use of the TIC s during the teaching and learning process. In this way, it is believed that the initial academic formation the privileged ORFXV for carring out this intent. Through the collected data from interviews, questionnaires and documental analysis, it is intended to comprehend the object of study by a complex articulation of events that have conditioned and determined the fall of traditional educational paradigm and has brought up a reflection about education theories and practices, with an eye on the reconfiguration of education as well as of teachers. The results point out the coexistence of critical and technical conceptions with the predominance of the technical approach in the talking and practices of those that took part in the research and highlight the nervy points that must be solved in order to anable the teachers and students of Pedagogy to obtain the necessary knowledge for construction of competences for the use of TIC s in the exercise of their profession.